Idebenone protects mitochondrial function against amyloid beta toxicity in primary cultured cortical neurons. Issue 15 (14th October 2020) - Wang, Huiting; Li, Lei; Jia, Kun; Wang, Qi; Sui, Shaomei; Lin, Yicheng; He, Yan
Abstract : Mitochondrial dysfunction has been repeatedly identified to be hallmark brain pathology underlying neuronal stress in Alzheimer's disease. As a result, mitochondrial medicine for the treatment of Alzheimer's disease has received increasing recognition. Idebenone (IDB) is a synthetic analog of Coenzyme Q10 (CoQ10) carrying antioxidizing property. Previous clinical trials reported a conflicting disease-modifying effect of IDB on Alzheimer's disease patients. However, whether IDB is preventive against amyloid beta (Aβ)-induced mitochondrial and neuronal stress has not been comprehensively investigated. In this study, we adopted an in-vitro setting by using primary cultured cortical neurons for the test. Neurons were pretreated with IDB prior to Aβ exposure. IDB pretreatment significant prevented neurons from Aβ-induced collapse of mitochondrial bioenergetics and perturbations of the protein kinase A (PKA)/cAMP response element-binding protein (CREB) signaling. Importantly, the treatment of IDB alone demonstrated an indiscernible side effect on the measured mitochondrial function, PKA/CREB signaling and neuronal viability. Therefore, our findings in together show a preventive effect of IDB against Aβ-mediated mitochondrial and neuronal injury. The use of IDB may hold potential to reduce the risk of Alzheimer's disease as a preventive strategy.